International Retail Banking as a Strategy: An Assessment - Tschoegl, Adrian E. (Journal of International Business Studies, 1987)
We assess the viability of a bank's strategy of entering into retail banking worldwide, wherever regulations permit, via a review of literature and evidence on foreign direct investment in banking. Issues we discuss include the roles of regulation, the costs of operating at a distance and in an unfamiliar environment, and the advantages or offsetting factors which foreign banks may possess relative to their local competitors. The factors the paper examines are uncompetitive host markets, product differentiation, economies of scale, management and technology, cost of capital, government support, and vertical integration.